The use of a special toothbrush for dental and oral hygiene in children with mild mental retardation - Lina Rismayani; Gita Indartri; Samjaji Samjaji (Center of Excellent (Pusat Unggulan Iptek), 2023)
Background: People with mental retardation are a condition with general intelligence functions that are below average accompanied by reduced ability to adapt (adaptive behavior), which begins to appear before the age of 18 years, people who are mentally retarded have intelligence development (intellectual) and experience difficulties in the process of learning and social adaptation. Purpose: the purpose of this study was to determine the effect of using a special toothbrush on oral hygiene for children with mild mental retardation at SLBN Cineam, Tasikmalaya Regency. Method: this type of research is a quasi-experimental design with a one-group pretest posttest control research design. Sampling with total sampling. The data obtained from this study were processed using the Wilcoxon test. Results: the results of the Wilcoxson test obtained a significance result of 0.000 <0.05 in the intervention group and the control group, which means that there is a significant effect of using a special toothbrush on the dental and oral hygiene of mentally retarded children. Conclusion: there is an effect of using a special toothbrush on dental and oral hygiene of children with mild mental retardation at SLBN Cineam, Tasikmalaya Regency.